2017
DOI: 10.1017/jfm.2017.693
|View full text |Cite
|
Sign up to set email alerts
|

Richtmyer–Meshkov instability of a thermal interface in a two-fluid plasma

Abstract: We computationally investigate the Richtmyer–Meshkov instability of a density interface with a single-mode perturbation in a two-fluid, ion–electron plasma with no initial magnetic field. Self-generated magnetic fields arise subsequently. We study the case where the density jump across the initial interface is due to a thermal discontinuity, and select plasma parameters for which two-fluid plasma effects are expected to be significant in order to elucidate how they alter the instability. The instability is dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(81 citation statements)
references
References 44 publications
2
79
0
Order By: Relevance
“…where m e;i are the electron and ion masses, e is the electron charge, n i is the ion number density, T is the temperature, k B is the Boltzmann constant, 0 is the vacuum permittivity, and ln K is the Coulomb potential which evaluates to be of order O (10) in most of the plasmas. The two-fluid plasma model, henceforth denoted as 2FP, is particularly relevant when the characteristic length scale is comparable to the ion skin depth, and the characteristic time scale is comparable to the ion cyclotron period.…”
Section: Introductionmentioning
confidence: 99%
“…where m e;i are the electron and ion masses, e is the electron charge, n i is the ion number density, T is the temperature, k B is the Boltzmann constant, 0 is the vacuum permittivity, and ln K is the Coulomb potential which evaluates to be of order O (10) in most of the plasmas. The two-fluid plasma model, henceforth denoted as 2FP, is particularly relevant when the characteristic length scale is comparable to the ion skin depth, and the characteristic time scale is comparable to the ion cyclotron period.…”
Section: Introductionmentioning
confidence: 99%
“…The extreme temperatures required for ICF implosion inevitably causes rapid ionization of the involved materials, which then leads to interaction between the conducting fluids and magnetic fields that are imposed or self-generated [9][10][11][12]. In order to model the coupled evolution of plasmas and magnetic fields, several theoretical descriptions have been considered.…”
Section: Introductionmentioning
confidence: 99%
“…Srinivasan and Tang [18] adopted the Hall-MHD model to examine the magnetic field generation and growth for the gravity induced Rayleigh-Taylor instabilities (RTI). More recently, Bond et al [12] investigated computationally the RMI without initial magnetic field using the ideal two-fluid plasma equations. In order of decreasing complexity, Shen et al [19] showed that the ideal two-fluid plasma equations, the Hall-MHD and regular MHD models, are connected via a series of limiting processes with respect to the appropriately scaled parameters including the speed of light, the ion skin depth, and ion-to-electron mass ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a shock which formation not mediated by collisionless plasma instabilities will not inherit the downstream electromagnetic patterns formed by these instabilities. Collisions of shells with curved boundaries may trigger downstream vorticity that could generate magnetic fields [54]. But colliding planar shells like those considered here, will yield a field-free downstream if the formation is collisional.…”
Section: Discussionmentioning
confidence: 88%